Successful Management of Infertility due to PCOS Using an Ayurvedic Regimen - Sonia Sharma; Bihani Sanjyal; B.Pushpalatha; K.Bharathi (AYUSHDHARA, 2023)
Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder that often leads to infertility due to irregular menstrual cycles and hormonal imbalances. This case report presents the successful management of infertility associated with PCOS using a comprehensive Ayurvedic regimen. Case Presentation: The case involves a 24 years old woman diagnosed with PCOS who had been struggling with infertility for 5 years. Intervention: The Ayurvedic treatment plan included dietary modifications, standard Ayurvedic treatment protocol along with lifestyle changes and stress management techniques. Outcomes: After one cycle of Yoga Basti, patient get urine pregnancy test positive in next cycle. Conclusion: This case highlights the potential efficacy of Ayurvedic interventions in managing infertility related to PCOS and emphasizes the importance of a holistic approach in healthcare.